The clinical evaluation of sepsis-1 and sepsis-3 in patients with acute surgical abdominal pathology - B. O. Matvijchuk; Y. A. Korol; Y. Z. Pater; R. L. Bokhonko; O. P. Tsymbala (Сучасні медичні технології)
Purpose of the study. Comparison Sepsis-1 and Sepsis-3 use in clinical practice at patients with acute surgical abdominal pathology.